(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Citizens of the Philippines responded in a significant and diverse way to the 2022 national election. Compared to previous elections in the Philippines, this election is extremely different. For young adults, different viewpoints and impressions regarding the choice of public leaders were a serious issue. It also seems new and unusual because every citizen is becoming more and more involved in politics. This phenomenon appeared without further research from earlier studies. The researcher decided to investigate and look for answers from this study. This study follows all necessary health protocols and collects data via a semi-structured interview. The findings showed the perceptions of the seven respondents toward the 2022 national election and how they were influenced and became aware of the situation during the 2022 national election period, which is represented by their insights and experiences that mostly overlap with each other. However, there were also perceptions that were freshly introduced by individual participants. Lastly, it aims to map out how these perceptions and experiences will improve the community’s ability to have an open conversation when it comes to politics and develop a peaceful election in the future. Moreover, three tables emerge from this study’s findings, namely: (1) ENGAGEMENT: Awareness and Participation; (2) Perceptual Set Determinants; and (3) Factors Influencing Individual Behavior.